2021
DOI: 10.1007/978-3-030-77371-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalysis: Introduction, Mechanism, and Effective Parameters

Abstract: The widely investigated heterogeneous photocatalysis offers an environmentally friendly, efficient, and versatile solution for several environmental problems. Among others, the removal of harmful organic pollutants and the generation of H 2 via water splitting are well-known and most widely studied applications. The process is based on the charge separation caused by the excitation of semiconductor photocatalyst via photon absorption. Due to the intensive development of material science, in addition to the wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 142 publications
(194 reference statements)
0
2
0
Order By: Relevance
“…10 , see Tables S5 and S6 ) revealed that the degradation efficiency of both dyes increased with reaction time, peaking at 10 min for crystal violet (95.70% degradation) and 15 min for methylene blue (95.15% degradation). Beyond these durations, the efficiency plateau due to the active sites on the photocatalyst surface may become saturated or deactivated over time, suggesting that extended reaction times did not yield further enhancements in degradation efficiency 57 .
Figure 10 Effect of reaction time on the catalytic degradation of CV and MB.
…”
Section: Resultsmentioning
confidence: 99%
“…10 , see Tables S5 and S6 ) revealed that the degradation efficiency of both dyes increased with reaction time, peaking at 10 min for crystal violet (95.70% degradation) and 15 min for methylene blue (95.15% degradation). Beyond these durations, the efficiency plateau due to the active sites on the photocatalyst surface may become saturated or deactivated over time, suggesting that extended reaction times did not yield further enhancements in degradation efficiency 57 .
Figure 10 Effect of reaction time on the catalytic degradation of CV and MB.
…”
Section: Resultsmentioning
confidence: 99%
“…Les OH • radicals are particularly reactive and can oxidize a wide range of organic compounds, leading to their decomposition into smaller, less toxic molecules [14]. This ability to decompose pollutants makes photocatalytic degradation a promising and effective method for water treatment.…”
Section: Introductionmentioning
confidence: 99%